THE INFLUENCE OF PRODUCT QUALITY AND M-BANKING SERVICE QUALITY ON CUSTOMER SATISFACTION OF BANK SHARIA INDONESIA WITH RELIGIUSITY AS A MODERATING VARIABLE - Nur Mija Hasibuan; Ahmad Perdana Indra (Jurnal Ekonomi, 2023)
With religiosity as a moderating variable for Bank Syariah Indonesia customers in North Padang Lawas Regency, the purpose of this study was to determine the relationship between customer satisfaction with Bank Syariah Indonesia and the quality of m-banking services and products. This study uses quantitative techniques with important information obtained from a survey of 100 respondents. The data analysis method used is Moderate Regression Analysis (MRA) and Multiple Linear Regression Analysis . The findings show that customer satisfaction is partially influenced by the quality of m-banking products and services, that these two factors simultaneously have a significant impact on customer satisfaction, and that religiosity is able to moderate the impact of these two factors on customer satisfaction. The findings of this study could have an important impact on promoting mobile banking to the general public and increasing customer satisfaction.